Safety and Feasibility of Esophagectomy Following Neoadjuvant Immunotherapy Combined with Chemotherapy for Esophageal Squamous Cell Carcinoma - Gu, Yi-Min; Shang, Qi-Xin; Zhang, Han-Lu; Yang, Yu-Shang; Wang, Wen-Ping; Yuan, Yong; Hu, Yang; Che, Guo-Wei; Chen, Long-Qi (Frontiers in Surgery, 2022)
Background: This study aimed to investigate the safety and feasibility of esophagectomy after neoadjuvant immunotherapy and chemotherapy for esophageal squamous cell carcinoma. Methods: We retrospectively identified patients who received neoadjuvant immunotherapy combined with chemotherapy (n=38) in our center between 2020 and 2021. The primary end point was the risk of major complications (grade 3) according to the Clavien–Dindo classification. Secondary end points were surgical details, 30-day mortality, and 30-day readministration. Results: The most commonly used regimens of immunotherapy were camrelizumab (36.8%), pembrolizumab (31.5%), tislelizumab (15.8%), sintilimab (13.2%), and toripalimab (2.6%). The median interval to surgery was 63 days (range, 40-147). Esophagectomy was performed in 37 of 38 patients who received neoadjuvant immunotherapy and chemotherapy. All procedures were performed minimally invasively, except for 1 patient who was converted to thoracotomy. Of 37 surgical patients, R0 resection was achieved in 36 patients (97.3%). Pathologic complete response was observed in 9 patients (24.3%). Tumor regression grade I was identified in 17 patients (45.9%). Morbidity occurred in 12 of 37 of patients (32.4%). The most common complication was pneumonia (16.2%). There were no deaths or readministration within 30 days. Conclusions: Esophagectomy following neoadjuvant immune checkpoint inhibitor plus chemotherapy for patients with resectable esophageal squamous cell carcinoma appears to be safe and feasible, with acceptable complication rates.